Some factors influencing social relations in Algerian sports clubs: A field study in the provinces of Setif, Bordj Bou Arreridj, M’Sila, Annaba, and El Tarf - baka, fares (sports creativity, 2025)
This research examines the social relationships within professional football teams in the first and second divisions and their influence by financial factors. The study focuses on two key indicators: the financial aspect of the relationship between players, coaches, and club management, as well as between coaches and club management; and the nature of the relationship itself—whether it is purely financial or cooperative. The descriptive method was employed to analyze the correlational relationships among a sample of players, coaches, and administrators. The study yielded the following results: - The relationships between the three parties in the sports club are primarily financial: between players and coaches, between players and management, and between coaches and management. - The club's sporting performance depends on the amount of financial expenditure incurred during the season.